Microstructure and mechanical properties of resistance-spot-welded joints for A5052 aluminum alloy and DP 600 steel - Chen, Jianbin; Yuan, Xinjian; Hu, Zhan; Sun, Changzheng; Zhang, Yanxin; Zhang, Yuxuan (Materials characterization, 2016)
The microstructure and mechanical properties of resistance-spot-welded A5052 aluminum alloy and DP 600 dual-phase steel joint were studied. The fusion zone (FZ) and heat-affected zone (HAZ) of DP 600 exhibited lath martensite and ferrite-martensite structures, respectively. The microstructure of FZ and HAZ in the A5052 side was composed of cellular crystals and the boundary region of FZ exhibited a columnar crystal morphology. A Fe2Al5 intermetallic compound (IMC) layer with 3.3μm thickness was found adjacent to the DP 600 side, whereas a needle-shaped Fe4Al13 IMC layer with length of 0.67μm to 15.8μm was found adjacent to the aluminum alloy side. The maximum tensile shear load of the A5052/DP 600 joint was 5.5KN, with a corresponding molten nugget diameter of 6.3mm. The fracture morphology of the optimized A5052/DP 600 joint was mainly an elongated dimple fracture accompanied by cleavage fracture. [Display omitted] •A5052 and DP 600 with large gaps in properties were investigated by RSW.•The microstructures of RSW joints in DP 600/A5052 were examined detailedly.•The micro/macro-characteristics and strength relations of joints were analyzed.